UBR5 inhibits the radiosensitivity of non-small cell lung cancer cells via the activation of the PI3K/AKT pathway. (2nd April 2021) - Gu, Yong-Fei; Ge, Xing-Ping
Abstract : Ubiquitin protein ligase E3 component n-recognin 5 (UBR5) has been identified as an oncogene in diverse cancers; however, whether its expression was associated with radiosensitivities of non-small cell lung cancer (NSCLC) cells remains unclear. Expression levels of UBR5 in NSCLC tissues and cell lines were examined by immunohistochemical staining and western blotting. Colony formation assay, CCK-8 cell viability assay, flow cytometry, and caspase-3 activity assay were performed to evaluate the radiosensitization of UBR5 knockdown in NSCLC cells, and the underlying mechanism in vitro was also investigated. UBR5 was highly expressed in NSCLC tissues, and its high expression was associated with the poor prognosis in 50 patients with NSCLC. After X-ray irradiation, the protein expression levels of UBR5 were also increased in NSCLC cells. UBR5 inhibition enhanced the radiosensitivity of NSCLC cells by inhibiting the cell viability and inducing apoptosis. Further investigation indicated that UBR5 knockdown-mediated radiosensitization involved the phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway. Knockdown of UBR5 radiosensitizes NSCLC cells via the inactivation of the PI3K/AKT signal, which provided a novel therapeutic target for NSCLC radiosensitization.